Augmented Reality Pada Metamorfosis Lebah (APIS SP.) Sebagai Media Pembelajaran - Meishanti, Ospa Pea Yuanita; Roziqo, Zaidatur (SAINTEKBU, 2021)
Augmented Reality is actually not something foreign to the general public, it's just that they don't know what Augmented Reality itself means, Augmented Reality cards can generally be found in some snacks, which the cards can be scanned through a special application available on the Playstore. However, currently researchers are making Augmented Reality for learning, in this case researchers are using bee metamorphosis, so learning becomes more interesting. This study aims to describe the feasibility of Augmented Reality media for bee metamorphosis and to determine student responses to the attractiveness of Augmented Reality media for bee metamorphosis. The development model used is the ADDIE model which includes: Analysis, Design, Development, Implementation and Evaluation. Products are validated by one media expert and one material expert. The attractiveness test was carried out on 5 students of MTs Al-Ihsan Kalijaring Jombang. Data obtained from media experts, namely 80% with proper qualifications, criteria from material experts, namely 88% with very decent qualifications, while from the data students get a score of 88.75% with qualifications strongly attractiveness. The results of the assessment of media experts, material experts and student responses show that the bee metamorphosis Augmented Reality can be used as a learning media.